Epidemiological trends in autism and other neurodevelopmental disorders in Kazakhstan (2016–2022): a regional and national perspective - Nukeshtayeva, Karina; Bolatova, Zhanerke; Galayeva, Aza; Shintayeva, Nurzhamal; Zhanalina, Gulmira (Frontiers in Psychiatry, 2025)
BackgroundThis study investigates the epidemiological trends of autism spectrum disorder and other neurodevelopmental disorders in Kazakhstan from 2016 to 2022.MethodsUtilizing national healthcare databases, we analyzed the incidence and prevalence of childhood autism, atypical autism, and neurodevelopmental disorders across various regions of Kazakhstan.ResultsOur findings reveal a nearly fivefold increase in the diagnosis of childhood autism and a fourfold increase in atypical autism over the seven-year period, with both trends showing statistical significance (p < 0.01). However, no significant trend was observed for broader neurodevelopmental disorders. Regional disparities were evident, with northern regions showing higher rates of ASD diagnoses compared to the southern regions, likely influenced by factors such as healthcare infrastructure, urbanization, and environmental pollution. Astana showed a marked increase in childhood autism prevalence, reaching 263.7 per 100,000 children by 2022.ConclusionData highlight an important public health trend in Kazakhstan, where the primary incidence of autism spectrum disorders is on the rise, reflecting improved recognition and diagnostic practices.